Diagnostic features research of ac electric point motors - Buryak, S. YU.; Gavrilyuk, V. I.; Hololobova, O. O.; Beznarytnyy, A. M. (Science and Transport Progress, 2014)
Purpose.Considerable responsibility for safety of operation rests on signal telephone and telegraph department of railway. One of the most attackable nodes (both automation systems, and railway in whole) is track switches. The aim of this investigation is developing such system for monitoring and diagnostics of track switches, which would fully meet the requirements of modern conditions of high-speed motion and heavy trains and producing diagnostics, collection and systematization of data in an automated way. Methodology. In order to achieve the desired objectives research of a structure and the operating principle description of the switch electric drive, sequence of triggering its main units were carried out. The operating characteristics and settings, operating conditions, the causes of failures in the work, andrequirements for electric drives technology and their service were considered and analyzed. Basic analysis principles of dependence of nature of the changes the current waveform, which flows in the working circuit of AC electric point motor were determined. Technical implementation of the monitoring and diagnosing system the state of AC electric point motors was carried out. Findings. Signals taken from serviceable and defective electric turnouts were researched. Originality. Identified a strong interconnectionbetween the technical condition of the track switchand curve shape that describes the current in the circuit of AC electric point motor during operation which is based on the research processes that have influence on it during operation. Practical value. Shown the principles of the technical approach to the transition from scheduled preventive maintenance to maintenance of real condition for a more objective assessment and thus more rapid response to emerging or failures when they occur gradually, damages and any other shortcomings in the work track switch AC drives.